Upaya Meningkatkan Hasil-hasil Belajar Siswa melalui Pembelajaran Berbasis Proyek pada Materi Mengembangkan Kemampuan Diriku di SDN 20 Laman Mumbung - Veronika Yunita (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve students' learning outcomes through the implementation of the Project-Based Learning (PjBL) model on the topic "Developing My Abilities" at SDN 20 Laman Mumbung for the 2024/2025 academic year. The background of this research is the low learning outcomes of students, both cognitive and affective, which necessitate an innovative approach in the learning process. This research employs a classroom action research method with two cycles involving 10 fourth-grade students. Data collection techniques include observation, tests, and questionnaires. The expected results are an improvement in both cognitive and affective learning outcomes, as well as increased active participation among students in the learning process. Through the implementation of PjBL, it is anticipated that students will gain a deeper understanding of the material and enhance their motivation to learn. This research is expected to contribute positively to teaching practices in the school.